Variation in birdsong of red vented bulbul (Pycnonotus cafer) Inhabiting two different locations - Manjunath, Manjunath; Joshi, Bhaskar (Journal of Experimental Sciences, 2013)
This species emits a high variety of acoustic signals in their communication. The signals may be long or short and simple; these signals can be classified into songs and calls. Individuals sang throughout the year. The songs of red-vented bulbul (pycnonotus cafer) in two regions: Gulbarga and Ainoli were studied during the period from March 2008 to June 2009. The results show that variations exist in this bird species. The songs of birds from two regions shows differences in the tone characteristics, number of syllables, duration, spectral features and frequency range of the main sentence and so on.